Aluminum alloy for low-friction sliding bearing and preparation method of aluminum alloy
By designing AG, CAF2, and Aln with self -lubrication functions in aluminum alloy sliding bearing, using high -energy laser beams to promote the original reaction to form a self -lubrication phase, solve the problem of high friction coefficient of existing aluminum alloy sliding bearing, and achieve significant reduction in significantly reduced reduction. The friction coefficient and the effect of the service life.
Patent Information
- Application Number
- CN202411482450.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-28
AI Technical Summary
The friction coefficient of existing aluminum alloy sliding bearings is high, resulting in insufficient service life. Especially in low-speed heavy loads and large impact loads, the friction coefficient is still large, affecting the wear resistance and service life of the bearing.
The design of an aluminum alloy by designing a low -slip dynamic shaft, including AG, CAF2, and Aln with a self -lubricating function formed by the substrate and the in situ reaction. Under the action of high -energy laser beams, the aluminum alloy is covered by aluminum covering CA3N2/AGF hybrid powder to produce F, CA, N, and covering aluminum in situ reactions. Deformation reduces friction.
A significant reduction of the friction coefficient of the sliding shaft to the aluminum alloy, improved the service life, the friction coefficient was reduced below 0.18, which was far lower than the friction coefficient of a single Al-SN alloy. Dysplasia.
Smart Images

Figure CN119372526A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an aluminum alloy for bearings, in particular to an aluminum alloy for low-friction sliding bearings and a preparation method thereof. Background Art
[0002] Sliding bearings consist of a bearing body and a bushing, and are mainly used to support rotating shafts or other moving bodies, guide rotation or movement, and bear the load transmitted by the shaft or parts on the shaft. They are mostly used in high-speed, heavy-load, and split-structure-required occasions, such as steam turbines, centrifugal compressors, internal combustion engines, and large motors. Sliding bearings are also often used in transmission equipment with low speed, heavy load, and large impact loads, such as stamping machinery, agricultural machinery, and crane equipment, and when the radial size is limited, such as multi-roll steel mills. Wear resistance is an important performance indicator for evaluating sliding bearings. At present, the industry mostly uses the hard matrix soft particle method to enhance wear resistance, that is, hard and brittle eutectic compounds are distributed on the harder aluminum solid solution matrix. These hard and brittle phases are easy to fall off from the aluminum matrix, become abrasive particles, scratch and wear the journal. Alloying is one of the main methods to improve the friction performance of aluminum-tin alloys. Adding alloying elements that are not soluble or have limited solid solution, such as tin, lead, zinc and silicon, has a low hardness. During the friction process, the wear of the hard relative journal can be avoided by relying on its own plastic deformation, but its friction coefficient is still large. In order to further improve the comprehensive performance of aluminum alloy bearing alloys, domestic and foreign researchers have conducted a lot of research.
[0003] Rare earth elements have high strength, good thermal conductivity and mechanical properties. Their solid solubility in aluminum alloys is low, causing rare earth solutes to be enriched at the solid-liquid interface and inhibiting grain growth. For example, the addition of Er and Zr can improve the wear resistance and hardness of Al-Sn alloys. As the load increases, the wear mechanism changes from abrasive wear, mild adhesive wear and slight stratified wear to severe adhesive wear and stratified wear. The friction coefficient curve of the rare earth La-strengthened Al-Sn alloy prepared by electromagnetic stirring technology has less fluctuation, and a smooth and continuous oxide film is formed on the wear surface, which plays a self-lubricating role. The average friction coefficient is reduced to 0.312 and the wear volume is reduced to 0.1168mm 3 . After adding the low-melting-point component Bi, a spherical Bi-rich phase appears in the alloy, and the alloy's anti-seizure ability is significantly improved. In addition, a band-shaped Bi-rich phase is found coated on the wear surface, which plays a role in reducing friction and self-lubricating. The above measures have improved the wear resistance of aluminum alloy sliding bearings to a certain extent. However, a single hard rare earth alloy element or soft metal element still has hard or soft contact with the journal, resulting in a high friction coefficient. Therefore, the development of aluminum alloys for low-friction sliding bearings can effectively solve the above key technical problems. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide an aluminum alloy for low-friction sliding bearings that reduces the friction coefficient of aluminum alloy sliding bearings and increases their service life.
[0005] Another object of the present invention is to provide a method for preparing an aluminum alloy for a low-friction sliding bearing, which reduces the friction coefficient of the aluminum alloy sliding bearing and increases the service life.
[0006] Technical solution: The aluminum alloy for low-friction sliding bearings described in the present invention includes a matrix and Ag, CaF2 and AlN with self-lubricating function formed by in-situ reaction.
[0007] Preferably, the Ag is decomposed from AgF in the aluminum-coated Ca3N2 / AgF mixed powder under the action of a high-energy laser beam.
[0008] Preferably, the CaF2 and AlN are formed by an in-situ reaction of F, Ca, N produced by decomposition of aluminum-coated Ca3N2 / AgF mixed powder and coated aluminum under the action of a high-energy laser beam.
[0009] The method for preparing the aluminum alloy for low-friction sliding bearings of the present invention comprises the following steps:
[0010] (1) mixing Ca3N2 and AgF powders by low temperature ball milling to obtain a mixed powder;
[0011] (2) depositing an aluminum layer on the surface of the mixed powder obtained in step (1) to obtain an aluminum-coated Ca3N2 / AgF mixed powder;
[0012] (3) ball-milling the aluminum-coated Ca3N2 / AgF mixed powder obtained in step (2) with aluminum alloy powder to obtain an aluminum alloy composite material powder;
[0013] (4) Using a high-energy laser beam to perform high-temperature scanning on the composite material powder obtained in step (3) to obtain an aluminum alloy for sliding bearings reinforced with Ag, CaF2 and AlN having a self-lubricating function.
[0014] Preferably, in the step (1), the mass ratio of Ca3N2 to AgF powder is 1:1.5 to 1:1.6, and more preferably 1:1.5.
[0015] Preferably, the ball milling temperature in step (1) is 0-5°C, preferably 5°C.
[0016] Preferably, the surface deposition in step (2) is performed using a cold spraying process.
[0017] Preferably, the cold spraying process parameters in step (2) are: pressure of 1.5 to 2.5 MPa, preferably 1.5 MPa; cold spraying time of 5 to 20 min, preferably 5 min.
[0018] Preferably, in step (3), the substrate is one of Al-Sn, Al-Si or Al-Ni, and more preferably an Al-Sn alloy.
[0019] Preferably, in step (3), the mass ratio of the Ca3N2 / AgF mixed powder to the aluminum alloy powder is 1:19 to 1:4, and more preferably 1:10.
[0020] Preferably, the scanning power of the high energy laser beam in step (4) is 325-400W, more preferably 325W.
[0021] Principle of the invention: The present invention is aimed at the design and manufacture of high-performance aluminum alloys for sliding bearings. In view of the high friction coefficient of aluminum alloys for sliding bearings, based on the self-lubricating function and physical properties of Ag, CaF2 and AlN, and according to the thermodynamic properties of the materials, an aluminum-coated Ca3N2 / AgF mixed powder reinforced aluminum alloy material system prepared by a composite process of ball milling and cold spraying is designed. The heat / mechanical interaction of a high-energy laser beam causes low-melting-point AgF and Ca3N2 to be decomposed into single-substance Ag and Ca, F and N components in sequence; at the same time, the high temperature of the laser beam induces an in-situ reaction between F / Ca and N / Al to generate CaF2 and AlN, which act as a solid self-lubricating functional phase during the friction process and can significantly reduce the friction coefficient. In addition, single-substance Ag acts as a soft point during the friction process, and its plastic deformation reduces damage to the bearing, thereby achieving low friction of aluminum alloys for sliding bearings.
[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0023] (1) This method is based on the solid self-lubricating function of CaF2 and AlN. According to the in-situ reaction of materials and thermodynamic principles, an aluminum-coated Ca3N2 / AgF mixed powder reinforced aluminum alloy material system is designed. Through the high-temperature induction of a high-energy laser beam, an in-situ reaction between F / Ca and N / Al is formed to form CaF2 and AlN self-lubricating functional phases. The CaF2 and AlN self-lubricating phases can enhance the interfacial bonding strength between them and the aluminum alloy matrix, effectively avoiding the wear of the bearing after the hard phase is peeled off from the matrix due to the weak interfacial bonding strength between the hard phase and the matrix during the friction process, and significantly reducing the friction coefficient of aluminum alloy used for sliding bearings.
[0024] (2) This method uses a high-energy laser beam to induce the decomposition of low-melting-point AgF to form elemental silver. During the friction process, the phase with lower hardness can reduce the friction between the aluminum alloy matrix and the shaft neck through its own plastic deformation, thereby achieving low friction of the aluminum alloy for sliding bearings. The friction coefficient of the aluminum alloy for sliding bearings prepared by the present invention is lower than 0.18, which is much lower than the friction coefficient of a single Al-Sn alloy.
[0025] (3) Under high temperature conditions, the solubility of silver in aluminum alloy is low, and the amount of silver dissolved in aluminum is low, which effectively avoids the precipitation of hard compound phases and the wear of the journal during the subsequent cooling process, thereby improving the service life of aluminum alloy for sliding bearings. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The microstructure diagram of the aluminum alloy for low-friction sliding bearing prepared in Example 1;
[0027] Figure 2 This is a schematic diagram of the change of the friction coefficient of the aluminum alloy for low-friction sliding bearings prepared in Example 4 over time;
[0028] Figure 3 The figure is a comparison chart of the friction coefficients of the aluminum alloys for sliding bearings prepared in Examples 1, 2, 3 and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below in conjunction with embodiments.
[0030] Example 1
[0031] The aluminum alloy for low-friction sliding bearings described in the present invention comprises a matrix, Ag, CaF2 and AlN formed in situ with self-lubricating function; the Ag is decomposed by AgF in aluminum-coated Ca3N2 / AgF mixed powder under the action of a high-energy laser beam; CaF2 and AlN are formed by in-situ reaction of F, Ca, N generated by decomposition of aluminum-coated Ca3N2 / AgF mixed powder and coated aluminum under the action of a high-energy laser beam.
[0032] The method for preparing the aluminum alloy for low-friction sliding bearings of the present invention comprises the following steps:
[0033] (1) In an inert argon atmosphere, Ca3N2 and AgF powders with a mass ratio of 1:1.5 were mixed by low-temperature ball milling at 5°C to obtain a mixed powder.
[0034] (2) Using a cold spraying process at a pressure of 1.5 MPa, an aluminum layer was deposited on the surface of the Ca3N2 / AgF mixed powder in step (1) for 5 minutes to obtain an aluminum-coated Ca3N2 / AgF mixed powder.
[0035] (3) Under an inert argon protection environment, the aluminum-coated Ca3N2 / AgF mixed powder described in step (2) and the Al-Sn alloy powder are ball-milled in a mass ratio of 1:19 to obtain an aluminum alloy composite material powder.
[0036] (4) A high-energy laser beam with a scanning power of 325 W is used to perform high-temperature scanning on the aluminum alloy composite material powder in step (3), so that AgF and Ca3N2 with lower melting points are decomposed into Ag, F, Ca and N elements in sequence, and CaF2 and AlN are in situ formed between F / Ca and N / Al under high-temperature induction, thereby obtaining an aluminum alloy for sliding bearings reinforced with Ag, CaF2 and AlN having a self-lubricating function.
[0037] Figure 1 The microstructure of the aluminum alloy for low-friction sliding bearings prepared in Example 1, wherein 1 is the CaF2 phase, 2 is the Ag phase, and 3 is the AlN phase. Figure 1 It can be found that the in-situ formed elongated self-lubricating phase CaF2, granular AlN and dendritic single Ag phase have no obvious metallurgical defects between the three self-lubricating phases and the aluminum alloy matrix, and have good interface bonding properties.
[0038] Example 2
[0039] The similarities between this embodiment and embodiment 1 are not repeated here, except that the aluminum alloy in step (3) is Al-Si, and the mass ratio of the Ca3N2 / AgF mixed powder to the aluminum alloy powder is 1:10.
[0040] Example 3
[0041] The similarities between this embodiment and embodiment 2 are not repeated here, except that the pressure in step (2) is set to 2.0 MPa.
[0042] Example 4
[0043] The similarities between this embodiment and embodiment 3 are not repeated here. The differences are as follows: in step (3), the mass ratio of the Ca3N2 / AgF mixed powder to the aluminum alloy powder is 1:4, and in step (4), the scanning power of the high-energy laser beam is 400 W.
[0044] The test method of the friction coefficient in the present invention is as follows: micro-friction is performed for 120 minutes under a positive pressure of 50N, GCr15 as a friction pair, and dry friction conditions.
[0045] Figure 2The friction coefficient of the aluminum alloy for low-friction sliding bearings prepared in Example 4 changes with time. It can be seen that in the whole process, the friction coefficient does not change much, about 0.11, indicating that the friction coefficient of the aluminum alloy prepared by this method is relatively stable. In the prior art, the friction coefficient of the Al-Sn-Si bearing alloy measured under dry friction conditions is about 0.33 (Shu Xiaofei. Effect of adding Si on the organizational structure and performance of mechanically alloyed Al-Sn bearing alloys [D]. South China University of Technology, 2012.). The friction coefficient of the aluminum alloy for low-friction sliding bearings prepared by the present invention is only one-third of that of the prior art, indicating that the in-situ formation of the self-lubricating phases CaF2, AlN and Ag phases can significantly reduce the friction coefficient of the sliding bearing aluminum alloy.
[0046] Comparative Example 1
[0047] The similarities between this embodiment and embodiment 1 are not repeated here. The difference is that instead of using Ca3N2 and AgF powder in step (1), only Al-Sn alloy powder is used to directly prepare aluminum alloy for sliding bearings using a high-energy laser beam.
[0048] Comparative Example 2
[0049] The similarities between this embodiment and embodiment 1 are not repeated here. The difference is that the aluminum-coated Ca3N2 / AgF mixed powder in step (2) is not used, and only Ca3N2, AgF and Al-Sn alloy powder are used to directly prepare aluminum alloy for sliding bearings using a high-energy laser beam.
[0050] The aluminum alloy prepared in Comparative Example 1 did not form a self-lubricating functional phase, and its friction coefficient was about 0.31, which was about twice the friction coefficient of the low-friction sliding bearing aluminum alloy prepared by the present method. The aluminum alloy prepared in Comparative Example 2 contained only two lubricating phases, Ag and CaF2, and its friction coefficient was about 0.23, which was still higher than the friction coefficient of the low-friction sliding bearing aluminum alloy prepared by the present method. It is shown that the three self-lubricating functional phases of CaF2, AlN and Ag formed in situ in the low-friction sliding bearing aluminum alloy prepared in the present application can effectively reduce the shear deformation and adhesion of the soft metal Sn during the friction process, thereby reducing the friction coefficient, further proving that the self-lubricating phase formed in situ in the present method can significantly reduce the friction coefficient of the sliding bearing aluminum alloy.
[0051] Figure 3 The figure is a comparison of the friction coefficients of the aluminum alloys for sliding bearings prepared in Examples 1, 2, 3 and Comparative Example 1. It can be found that the friction coefficients of the aluminum alloys for sliding bearings prepared in Examples 1, 2 and 3 are all lower than 0.18, much lower than the friction coefficient of a single Al-Sn alloy (about 0.31), and lower than the friction coefficient of an aluminum alloy containing only two lubricating phases of Ag and CaF2 (about 0.23), indicating that the method can effectively reduce the friction coefficient of the aluminum alloy for sliding bearings.
Claims
1. An aluminum alloy for low-friction sliding bearings, characterized in that: The invention comprises a matrix and Ag, CaF2 and AlN with self-lubricating function generated by in-situ reaction.
2. The aluminum alloy for low-friction sliding bearing according to claim 1, characterized in that: The Ag is decomposed from the AgF in the aluminum-coated Ca3N2 / AgF mixed powder under the action of a high-energy laser beam.
3. The aluminum alloy for low-friction sliding bearing according to claim 1, characterized in that: The CaF2 and AlN are formed by in-situ reaction of F, Ca, N generated by decomposition of aluminum-coated Ca3N2 / AgF mixed powder and coated aluminum under the action of a high-energy laser beam.
4. A method for preparing an aluminum alloy for a low-friction sliding bearing according to claim 1, characterized in that: The following steps are involved: (1) mixing Ca3N2 and AgF powders by low temperature ball milling to obtain a mixed powder; (2) depositing an aluminum layer on the surface of the mixed powder obtained in step (1) to obtain an aluminum-coated Ca3N2 / AgF mixed powder; (3) ball-milling the aluminum-coated Ca3N2 / AgF mixed powder obtained in step (2) and the matrix powder to obtain a composite material powder; (4) A high-energy laser beam is used to perform high-temperature scanning on the composite material powder obtained in step (3) to obtain an aluminum alloy for sliding bearings reinforced with Ag, CaF2 and AlN having a self-lubricating function.
5. The preparation method according to claim 4, characterized in that: In the step (1), the mass ratio of Ca3N2 to AgF powder is 1:1.5 to 1:1.6, and the ball milling temperature is 0 to 5°C.
6. The preparation method according to claim 4, characterized in that: The surface deposition in step (2) is performed by cold spraying process.
7. The preparation method according to claim 6, characterized in that: The cold spraying process parameters in step (2) are: pressure of 1.5-2.5 MPa and time of 5-20 min.
8. The preparation method according to claim 4, characterized in that: In the step (3), the matrix is one of Al-Sn, Al-Si and Al-Ni.
9. The preparation method according to claim 4, characterized in that: In the step (3), the mass ratio of the Ca3N2 / AgF mixed powder to the aluminum alloy powder is 1:19 to 1:
4.
10. The preparation method according to claim 4, characterized in that: The scanning power of the high energy laser beam in step (4) is 325-400W.